Interrogating What RemainsInviting Learners to Explore Cultural Artifacts from the Past - Marilyn McKinley Parrish; Carla Rineer (Adult Education Research Conference, 2015)
This paper explores the theoretical basis for the practice of investigating cultural artifacts in order to gain deeper understanding about the values, meanings and contexts of other time periods and cultures. Adult learners are invited to view culture from the margins through an exploration of the lives of people whose race, class, and gender form the basis of oppression by the powerful. Texts and narratives that provide evidence of daily-ness and ordinary-ness will be featured and implications of this engagement for adult learners will be explored.
Keywords: adult learning; cultural artifacts; primary sources; critical reflection; archives